(untitled) (Hekima Review, 2026)
The author proposes that the Good Samaritan in Jesus’s parable is a prophet. The prophetic act is to stop, refusing to pass by the one in distress. The article analyses what it means to be a prophet, one called to be a mediator in a time of crisis. The prophet offers hope, a hope born in an act of faith, based on the conviction that God desires good for humanity. This hope shines out in a time of crisis,remembering the God who has not allowed evil to triumph in the past, most paradigmatically leaving the tomb of Christ empty. The article then examines how a university might be a prophetic voice today by taking up the prophetic mantle and setting out on a journey that is intellectual as well as spiritual, social, active and creative. Focusing on the margins, the prophetic university makes them the centre of reflection.